Cuidados de Enfermería en pacientes con Depresión Posparto. - Lluguin Silva, Andrea Katherine (2025)
This research work demonstrates that postpartum depression (PPD) is a public health problem that affects women during pregnancy and after childbirth. According to the WHO, 300 million people in the world suffer from this disease. In Ecuador, its prevalence ranges between 50% and 85%, and in Riobamba, 34.6% of the patients who attended the Lizarzaburu Type C Health Center have presented PPD. In this study, we reviewed the scientific literature published between 2020 and 2025, collected from databases such as Scielo, PubMed, Google Scholar, and official agency documents. The main risk factors identified were: family problems, stressful events, history of mental disorders, low educational level, and limited access to health services. Symptoms include irritability, anxiety, excessive worry, and confusion, which can be assessed using the Edinburgh Postpartum Depression Scale (EPDS). The importance of nursing care, based on Cheryl Tatano's theory, is highlighted, focusing on comprehensive interventions that span from prevention to care, with a focus on the physical and psychological well-being of the mother.